Community-based interventions for criminal offenders with severe mental illness - Fisher, William H. (Amsterdam ; Boston : JAI, 2003)
People with mental illness in the criminal justice system are a vexing problem in many countries. Efforts to cope with this problem have taken a number of forms. Some focus on the expansion of existing community mental health treatment and support systems. Other, more recently developed approaches, such as jail diversion programmes and mental health courts, seek to move offenders with mental illness charged with "low-level" crimes from the criminal justice system to the mental health system. Others target offenders with mental illness who are being released from correctional settings, and attempt to facilitate their re-entry into the community and mental health service system. Whether and to what extent any of these efforts achieve their goals remains a significant question for researchers from a range of disciplines and for actors and stakeholders from various sectors of the mental health and criminal justice systems. The chapters presented in this volume explore key issues in this area, including the role of mental illness in criminal justice involvement, the effectiveness of psychopharmacologic and traditional community mental health treatment modalities, and the conceptualization and potential efficacy and effectiveness of new community-based approaches for serving offenders with mental illness.
Introduction / William H. Fisher -- Where is the 'illness' in the criminalization of mental illness? / Jeffrey Draine -- Community mental health services and criminal justice involvement among persons with mental illness / William H. Fisher, Nancy Wolff and Kristen Roy-Bujnowski -- Case management and the forensic client / Phyllis Solomon -- The impact of 'new generation' anti-psychotic medication on criminal justice outcomes / John A. Pandiani, Steven M. Banks and Sheila M. Pomeroy -- Jail diversion for people with mental illness: what do we really know? / Rani A. Desai -- The nature of the alliance: an anthropological look at the practice of forensic psychiatry / Dena Plemmons -- Courting the court: courts as agents for treatment and justice / Nancy Wolff -- Prison, hospital or community: community re-entry and mentally ill offenders / Stephanie Hartwell.
Includes bibliographical references.
Description based on print version record.
Keywords: Community mental health services -- United States; Mentally ill offenders -- United States; Mentally ill offenders -- Services for -- United States; Rehabilitation of offenders; Illness & addiction -- Social aspects; Psychology -- Mental Illness; Psychology -- Social Psychology